Augustus’ Reforms in the Munera Gladiatoria - Mauricio Pastor Muñoz (Gerión, 2017)
The munera gladiatoria were the most popular ludi among those offered in Rome and the other provinces of the Empire. Augustus played a crucial role in the history of the profession of gladiator. In fact, during the Empire, politicians were no longer able to decide about the munera. Rather, it was only the emperor who had any authority over the games. Augustus used the munus as one of the instruments to build his Empire. In that respect, he decided to provide gladiator performances with an organized structure, devising a meticulous system of regulations. This paper analyzes Augustus’ reformations and the impact they had on gladiator fights, which so much entertained Roman audiences.